The Effect of Na2SO4 and NaCl Solutions on the Moisture Movement of Fired Clay Masonry Wall - wan ibrahim, mohd haziman bin; Abu Bakar, Badorul Hisham; Johari, Megat Azmi Megat; Jaya, Ramadhansyah Putra; Arshad, Mohd Fadzil (International Journal of Sustainable Construction Engineering and Technology, 2011)
The influence of sodium sulphate and sodium chloride exposures on the moisture movement of masonry systems has been investigated. The investigation involved the measurement of moisture movement of single leaf masonry wall which were built with fired clay bricks in conjunction with grade (iii) mortar with proportions of 1: 1: 6 (OPC: lime: sand).  After being constructed, the masonry walls were cured under polythene sheet for 14 days in a controlled room with temperature of 25 ± 2ºC and 80 ± 5% relative humidity.  They were then exposed to sodium sulphate and sodium chloride solutions at different concentrations of 5, 10 and 15%. The moisture movement was monitored up to 210 days.  The moisture movement was also measured on the unbonded bricks and mortar prism so that the contribution of brick and mortar on the moisture movement of the masonry walls could be quantified. As a result, after the period of exposure to the soluble salt conditions, large expansion was observed in particular case of sulphate exposure. The composite model underestimated the moisture movement of fired clay masonry walls which were exposed to the soluble salts.